Upaya Pencegahan Ketergantungan NAPZA Pada Generasi Muda Di Kelurahan Bulang Lintang - Suci Fitriani; Aprilya Sri Rachmayanti; Habibie Habibie (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
NAPZA is an abbreviation of narcotics, psychotropics and addictive substances. Drug abuse is not only dangerous and detrimental to the family, but has broad social impacts. The Prevention, Eradication of Drug Abuse and Illegal Trafficking (P4GN) program needs to be carried out by focusing on prevention activities as an effort to make workers have the mindset, attitude and skills to reject drug abuse and illicit trafficking. It is hoped that this research can illustrate the effectiveness of the P4GN program outreach in preventing drug abuse among workers. The research was conducted in 2014 and carried out on 50 loading and unloading workers at Trisakti Port, Banjarmasin. The research instrument used a questionnaire and educational media. Before the extension is carried out, a pre-test and post-test are given after the extension to assess the effectiveness of the P4GN extension. The results of the analysis using the Wilcoxon test showed that there was a significant difference in knowledge between before the counseling and after the counseling was carried out. It is hoped that this research can increase the workforce's knowledge of drugs so that they can avoid drug abuse.